Harnessing Unconventional T Cells for Immunotherapy of Tuberculosis - La Manna, Marco P.; Orlando, Valentina; Tamburini, Bartolo; Badami, Giusto D.; Dieli, Francesco; Caccamo, Nadia (Frontiers in Immunology, 2020)
Even if the incidence of tuberculosis (TB) has been decreasing over the last years, the number of patients with TB is increasing worldwide. The emergence of multidrug-resistant and extensively drug-resistant TB is making control of TB more difficult. Mycobacterium bovis bacillus Calmette–Guérin vaccine fails to prevent pulmonary TB in adults, and there is an urgent need for a vaccine that is also effective in patients with human immunodeficiency virus (HIV) coinfection. Therefore, TB control may benefit on novel therapeutic options beyond antimicrobial treatment. Host-directed immunotherapies could offer therapeutic strategies for patients with drug-resistant TB or with HIV and TB coinfection. In the last years, the use of donor lymphocytes after hematopoietic stem cell transplantation has emerged as a new strategy in the cure of hematologic malignancies in order to induce graft-versus leukemia and graft-versus-infection effects. Moreover, adoptive therapy has proven to be effective in controlling cytomegalovirus and Epstein-Barr virus reactivation in immunocompromised patients with ex vivo expanded viral antigen-specific T cells. Unconventional T cells are a heterogeneous group of T lymphocytes with limited diversity. One of their characteristics is that antigen recognition is not restricted by the classical major histocompatibility complex (MHC). They include CD1 (cluster of differentiation 1)–restricted T cells, MHC-related protein-1–restricted mucosal-associated invariant T (MAIT) cells, MHC class Ib–reactive T cells, and γδ T cells. Because these T cells are genotype-independent, they are also termed “donor unrestricted” T cells. The combined features of low donor diversity and the lack of genetic restriction make these cells suitable candidates for T cell–based immunotherapy of TB.